Smart Grids and Load Profiles in the GCC Region - Safak Bayram, Islam (EAI Endorsed Transactions on Smart Cities, 2017)
The members of the Gulf Cooperation Council (GCC), namely Qatar, Bahrain, Saudi Arabia, Kuwait, Oman, and United Arab Emirates (UAE), are facing challenges to meet the growing electricity demand and reduce the associated hydrocarbon emissions. Recently, there has been a pressing need for a shift towards smart power grids, as smart grids can reduce the stress on the grid, defer the investments for upgrades, improve the power system efficiency, and reduce emissions. Accordingly, the goal of this paper is to delineate an overview of current smart grid efforts in the GCC region. First, we present a detailed overview of the current state of the power grids. Then, we classify the efforts into three broad categories: (i) energy trading and exchange through GCC interconnection; (ii) integration of renewable resources; and (iii) demand side management technologies for shaping the demand profile. Furthermore, we provide the details of our API object level real-time GCC power demand automated program that creates the database for the load profiles of the GCC members. Accessing such information for research and development purposes is a critical step in the region, because due the conservative structure of the governing institutes, there is no publicly available dataset. Therefore, the data provided in this paper is critical and will serve as a main reference for the future research efforts.